INTEGRASI ANALYTICAL HIERARCHY PROCESS DAN KRALJIC'S PURCHASING PORTFOLIO MODEL DALAM PENENTUAN STRATEGI PEMBELIAN MATERIAL PADA PT. FGH - Irfan Yodasaputra (2020)
PT. FGH is a food industry company that produces wafers. In performing the procurement, PT. FGH carries out the process of purchasing materials from outside parties (supplier). But in procurement activities there are still material purchases at PT.FGH that are not in accordance with the planning and still not good enough. This is due to late delivery or arrival of material. The discrepancy shows that the purchasing process was still not optimal. One of the efforts in performing a control over the problem is by developing an effective and optimal material purchasing strategy so as to minimize the risks that will occur. The preparation of a material purchasing strategy is determined by using one approach of Multi-Criteria Decision Making, namely the Analytical Hierarchy Process (AHP) method and the Kraljic's Purchasing Portfolio Model method. The Analytical Hierarchy Process (AHP) method is used to determine the weight value of supply risk and profit impact. The Kraljic's Purchasing Portfolio Model method is divided into four quadrants namely routine, bottleneck, leverage, and strategic where the quadrant is divided based on the weight of supply risk and profit impact criteria that will provide information about the characteristics of the purchase item. Based on the results of the study, it was found there are 4 materials in the non-critical items quadrant and 5 materials in the strategic items quadrant. This study aims to obtain the design of material purchasing strategies using the Kraljic's Purchasing Portfolio Model and AHP methods.